FATWA KONTROVERSIAL CRLO DALAM PANDANGAN KHALED ABOU EL FADL (Studi Kritik Otoritarianisme Fiqh) - Iman Fadhilah (Jurnal Iqtisad, 2017)
El Fadl parse some CRLO fatwa that is considered controversial and not oriented to benefit. Among the controversial fatwa is considered Case On Bra, high heeled shoes and Marriage Covenant, slander arising from Bury Pilgrimage Practices for Women, Devil In Cars and Danger Woman Traveling Without Mahram on prostration husband and wife as a submission to the husband.At least , to find out the methodological framework of thought El Fadl can be observed from some analysis tehadap contemporary theme of Islamic world. El Fadl, tried to analyze the sociological aspects of women’s lives in Saudi and the things that cause them to have less decent position in society . Sociological and political aspects in Arabic which causes them to have less decent position in society .Here then it can be stated that, El Fadl seeks to reposition religion critically, rationally and liberal, reconstruct Islamic heritage by giving new interpretations. For indeed, Muslims have the culture and traditions ( Turath ) nice and steady.